Respuesta :

Answer:

Q1.Let's solve your equation step-by-step.

2(x+3)=5x+6−3x

Step 1: Simplify both sides of the equation.

2(x+3)=5x+6−3x

(2)(x)+(2)(3)=5x+6+−3x(Distribute)

2x+6=5x+6+−3x

2x+6=(5x+−3x)+(6)(Combine Like Terms)

2x+6=2x+6

2x+6=2x+6

Step 2: Subtract 2x from both sides.

2x+6−2x=2x+6−2x

6=6

Step 3: Subtract 6 from both sides.

6−6=6−6

0=0

Answer:

All real numbers are solutions.

Q2.x−3=2x−3−x

Step 1: Simplify both sides of the equation.

x−3=2x−3−x

x+−3=2x+−3+−x

x−3=(2x+−x)+(−3)(Combine Like Terms)

x−3=x+−3

x−3=x−3

Step 2: Subtract x from both sides.

x−3−x=x−3−x

−3=−3

Step 3: Add 3 to both sides.

−3+3=−3+3

0=0

Answer:

All real numbers are solutions.

Q3.3(x−5)=2(x−5)+x

Answer:

There are no solutions.

Step-by-step explanation:

Hope I helped

Brainliest plz

Answer:

1. 8

2. -3

3. -15 or -10

Step-by-step explanation:

ACCESS MORE